A conceptual framework to guide the development of a transition support programme to facilitate the competencies of newly qualified registered nurses at public hospitals in Namibia - Emvula, Olivia; Pretorius, Louise; Amakali-Nauiseb, Taimi (International Journal of Health, 2022)
Purpose: Newly qualified registered nurses often lack the competence to efficiently execute their professional roles and responsibilities. They might fail to execute their nursing functions and make clinical judgement because of lack of confidence. The aim of the study is to develop a conceptual framework as basis for the development of a transition support programme to facilitate the competencies of newly qualified registered nurses (NQRNs) at public hospitals in Namibia. Methods: The Programme Logic Model (Knowlton & Phillips, 2013 was adapted as it allowed the researcher to present the conceptual framework in a systematic and visual way, while presenting and sharing the ideas and understanding of the relationships among the resources needed to develop the transition support programme, the planning of programme activities, and the changes or results you hope to achieve. Results: The results of the development of the conceptual framework served as basis for the transition support programme to facilitate the competencies of newly qualified registered nurses. Conclusion: The conceptual framework could serve an effective tool in guiding the development of the transition support programme to facilitate the competencies of newly qualified registered nurses.